Juridical Analysis Of The Reasons For The Annulment Of International Arbitration Awards By The Supreme Court In Decision No. 219 B/Pdt.Sus-Arbt/2016 - M susilo agung saputro, Agung; Lauren B. Edelman (Universitas Duta Bangsa Surakarta, 2025)
There are often obstacles in the recognition and enforcement of international arbitration awards, particularly concerning annulment grounds submitted to the Supreme Court, such as procedural non-compliance, allegations of fraud, and inconsistencies with the arbitration agreement, which may affect confidence in arbitration as a dispute resolution mechanism. This study aims to explore the mechanisms, challenges, and implications of annulment, as well as comprehensively examine the legal foundations underlying decisions and their impact on the parties' trust in arbitration. The research employs a normative juridical approach, with the results analyzed qualitatively. The findings indicate that the Supreme Court of the Republic of Indonesia plays a crucial role in annulling international arbitration awards based on national law and the principles of justice, especially in cases involving procedural violations or conflicts with public interest. The Supreme Court's rulings in international arbitration cases have significant legal implications, including clarifying the requirements for arbitration award recognition, enhancing legal certainty for investors, and strengthening Indonesia's legal standing in international agreements. While Supreme Court decisions may reinforce the arbitration system, diverse perspectives exist among stakeholders—business actors and investors may be concerned about legal uncertainty, whereas regulators and legal practitioners view such rulings as essential for maintaining arbitration integrity. Therefore, consistency, transparency, and the strengthening of arbitration regulations are key factors in sustaining trust in Indonesia's arbitration system.